Foccα6, a truncated nAChR subunit, positively correlates with spinosad resistance in the western flower thrips, Frankliniella occidentalis (Pergande). (August 2018) - Wan, Yanran; Yuan, Guangdi; He, Bingqing; Xu, Baoyun; Xie, Wen; Wang, Shaoli; Zhang, Youjun; Wu, Qingjun; Zhou, Xuguo
Abstract: Nicotinic acetylcholine receptors (nAChRs), a molecular target for spinosyns and neonicotinoids, mediate rapid cholinergic transmission in insect central nervous system by binding acetylcholine. Previous studies have shown that mutations in nAChRs contribute to the high level of resistance to these two classes of insecticides. In this study, we identified nine nAChR subunits from a transcriptome of the western flower thrips, Frankliniella occidentalis, including α1-7, β1, and β2. Exon 4 of α4 and exons 3 and 8 of α6 each have two splicing variants, respectively. In addition, altered or incorrect splicing leads to truncated forms of α3, α5, and α6 subunits. The abundance of every nAChRs in both spinosad susceptible and resistant strains was highest in the 1st instar nymph. Significantly more truncated forms of α6 subunit were detected in spinosad resistant strains, whereas, hardly any full-length form was found in the two highly resistant F. occidentalis strains (resistance ratio >10 4 -fold). Under laboratory conditions, spinosad resistance was positively correlated with truncated α6 transcripts. The correlation was later confirmed under the field conditions using five field strains. As the molecular target of spinosad, the percentage of truncated nAChR α6 subunits can be used as a diagnostic tool to detect and quantify spinosad resistance in the field. Graphical abstract: Image 1 Highlights: Nine nAChR subunits were identified and characterized from the Frankliniella occidentalis. nAChR subunits between spinosad susceptible and resistant F. occidentalis were comparatively investigated. Truncated α6 subunits were dominated in spinosad resistant strains. Spinosad resistance level was positively correlated with the percentage of truncated α6 subunit. Truncated Foccα6 represents a novel diagnostic marker to detect and quantify spinosad resistance in the field.